Gut Permeability and Microbiota in Parkinson’s Disease: Mechanistic Insights and Experimental Therapeutic Strategies - Liang, Yicheng; Zhao, Yuhang; Fasano, Alessio; Su, Chien-Wen (International journal of molecular sciences, 2025)
Globally, Parkinson’s disease (PD) is the neurodegenerative condition with the most rapidly increasing prevalence, and a growing body of evidence associates its pathology with impairments in the gut–brain axis. Traditionally viewed as a disease marked by the loss of dopaminergic neurons, emerging evidence emphasizes that chronic neuroinflammation is a driver of neurodegeneration, with gut-originating inflammation playing a crucial role. Increased intestinal permeability, often called “leaky gut,” allows harmful substances, toxins, and misfolded α-synuclein into the systemic circulation, potentially exacerbating neuroinflammation and spreading α-synuclein pathology to the brain through the vagus nerve or compromised blood–brain barrier (BBB). This review synthesizes current insights into the relationship between gut health and PD, emphasizing the importance of gut permeability in disrupting intestinal barrier function. This paper highlights innovative therapeutic approaches, particularly personalized therapies involving gut microbiome engineering, as promising strategies for restoring gut integrity and improving neurological outcomes. Modulating specific gut bacteria to enhance the synthesis of certain metabolites, notably short-chain fatty acids (SCFAs), represents a promising strategy for reducing inflammatory responses and decelerating neurodegeneration in Parkinson’s disease.